The CIA as organized crime: how illegal operations corrupt America and the world - Valentine, Douglas (Clarity Press, Inc., 2017)
"This book provides a cross-section of Douglas Valentine's investigations into CIA engagement in terrorism, drugs, and propaganda. Author of three books on CIA operations, Valentine's research into CIA activities began when CIA Director William Colby gave him free access to interview CIA officials who had been involved in various aspects of the Phoenix program in South Vietnam. It was a permission Colby was to regret. The CIA would rescind it, making every effort to impede publication of The Phoenix Program, which documented the CIA's elaborate system of population surveillance, control, entrapment, imprisonment, torture and assassination in Vietnam."--Publisher description